Codificação neural de estímulos visuais ecologicamente realísticos - João Vicente Dornas de Carvalho Silva (2013)
Neurons of visual areas, such as simple and complex cells of V1, have distinct electrophysiological responses when stimulated with natural scene images compared to responses due to artificial stimuli. In addition to the already known result on suppression caused by the contour in the Classical Receptive Field (CRF) when cells are stimulated with artificial stimuli, we also know that the selectivity (sparseness) of the response increases as a whole for natural scenes. While several studies have been done mainly in mammals, such as primates and felines, little is known about this difference in electrophysiological dynamics in birds. In this work we seek to understand how the electrophysiological response of neurons of the visual wulst of owls, which have physiology similar to V1 cells in primates, are characterized in relation to selectivity and center contour modulation when stimulated with natural scenes. Therefore, we carried out two experiments in order to understand how the temporal (first experiment) and spatial (second experiment) structure of a film with ecologically realistic scenes are presented in neuronal activity. In the first experiment, we present to the owl the same film, in full screen, in two time directions: direct and reverse. In the second experiment, we used stimuli from natural scene films that covered only the CRF or CRF together with ECRF (Extra Classical Receptive Field). In the first experiment, by reversing the tracks obtained with the reverse film and calculating the entropy of the Metric Space method along with the direct film tracks we noticed a significant increase in most protocols, which indicates that some cells have great sensitivity to the temporal structure of the stimulus, while others show to be sensitive only to the spatial aspect of the image. In the second experiment, we noticed an increase in selectivity, when we stimulated ECRF, along with a facilitation of neural response, in the vast majority of cases. We conclude that the neural activity of the complex cell can integrate input signals in different periods of time, and it is not possible in the present study to measure the exact magnitude of this period. And in contrast to the other species commonly studied, the owl’s complex cell increases its metabolic expenditure by causing facilitation during ECRF stimulation, which is represented by increased activity.